2−DIMENSIONAL IMPLEMENTATION OF THE FINITE−ELEMENT METHOD WITH SINGULARITY CORRECTION FOR DIFFUSION−LIMITED CURRENT AT AN UNSHIELDED DISC ELECTRODE - Galceran, J; Gavaghan, D; Rollett, J (1995)
Steady-state and time-dependent currents under diffusion limited conditions for a circular microelectrode embedded in insulating material are computed using the finite element method. A locally valid series expansion is used to correct for the boundary singularity at the electrode edge. By incorporating this correction into the equations of the finite element method in a fully implicit